Influence of irradiance and exposure time on the degree of conversion and mechanical properties of a conventional and silorane composite - M R Gonzalez; L T Poskus; HR Sampaio Filho; C R Perez (Wolters Kluwer Medknow Publications, 2013)
Aim: The aim of this study is to evaluate the influence of different combinations of irradiance and exposure time for a given radiant exposure on the degree of conversion (DC) and on the mechanical properties of two resin composites: Filtek Z250 and Filtek P90 LS (3M ESPE). Materials and Methods: The following curing protocols were used: Standard irradiance: 400 mW/cm2 for 60 s; Medium irradiance: 700 mW/cm2 for 34 s and High irradiance: 950 mW/cm2 for 26 s. The DC was measured using Fourier Transform Infrared spectroscopy. Each specimen was submitted to five indentations to evaluate the Knoop microhardness (KHN). The flexural strength (FS) was obtained from the three-point bending test. Cylindrical specimens were prepared for the Diametral tensile strength (DTS) test. Statistical analysis: Data were evaluated using two-way ANOVA and Tukey's test (α = 0.05). Results: DC and DTS were not influenced by the different curing protocols. For P90, the medium irradiance showed higher values of KHN than the standard irradiance. For Z250, the high irradiance showed higher values of FS than the standard irradiance. Conclusion: The influence of the different combinations of irradiance and exposure time depends on the resin composite as well as the specifically evaluated mechanical property.